PENGARUH LAMA PERENDAMAN DALAM EKSTRAK BAWANG MERAH TERHADAP INVIGORASI DUA VARIETAS BENIH CABAI RAWIT (Capsicum frutescens L.) KADALUWARSA - Rizaldi, Rafli; Yenny, Ratna Fitry; Hilal, Samsu; Sodiq, Abdul Hasyim (Fakultas Pertanian, Universitas Janabadra, 2024)
The problem of using seeds that exceed the expiration date is one of the causes of the decline in chili production in Banten Province. This study aims to determine the length of soaking in shallot extract on the invigoration of two expired varieties of cayenne pepper (Capsicum frutescens L). The experimental design used was a Completely Randomized Factorial Design which consisted of two factors, namely soaking time and type of cayenne pepper variety. The first factor, namely the soaking time for shallot extract (L), consists of 3 levels, including soaking time of 4 hours, 8 hours and 12 hours. Meanwhile, the second factor is the type of cayenne pepper variety (V), consisting of 2 levels, including the Madun variety and the Genie variety. The results showed that the length of soaking in shallot extract had no significant effect on the parameters of growth speed, number of leaves, simultaneous growth of sprouts, percentage of germination, and root length. Apart from that, there was no interaction between the length of soaking and the type of expired cayenne pepper variety. However, the Madun and Genie cayenne pepper varieties differed in their responses to almost all the parameters observed. Keywords: soaking time, onion extract, invigoration, expiration, cayenne pepper INTISARIPermasalahan penggunaan benih yang melampaui batas waktu penggunaan (kadaluwarsa) menjadi salah satu penyebab turunnya produksi cabe di Provinsi Banten. Penelitian ini bertujuan untuk mengetahui lama perendaman dalam ekstrak bawang merah terhadap invigorasi dua varietas cabai rawit (Capsicum frutescens L) kadaluwarsa. Rancangan percobaan yang digunakan adalah Rancangan Acak Lengkap Faktorial yang terdiri dari dua faktor, yaitu lama perendaman dan varietas cabai rawit. Faktor pertama adalah lama perendaman ekstrak bawang merah (L) terdiri dari 3 taraf, yaitu lama perendaman 4 jam, 8 jam, dan 12 jam. Faktor kedua adalah varietas cabai rawit (V), terdiri atas dua taraf, yaitu varietas Madun dan varietas Genie. Hasil penelitian menunjukkan bahwa lama perendaman dalam ekstrak bawang merah tidak berpengaruh nyata terhadap parameter kecepatan tumbuh, jumlah daun, keserempakan tumbuh kecambah, persentase daya kecambah, dan panjang akar. Selain itu tidak terdapat interaksi antara lama perendaman dan jenis varietas cabai rawit kadaluwarsa. Namun antara varietas cabai rawit Madun dan Genie berbeda tanggapannya terhadap hampir semua parameter yang diamati. Kata kunci: lama perendaman, ekstrak bawang merah, invigorasi, kadaluwarsa, cabai rawit